The rules of comparative fiqh in modern fatwa and legal reform - Adb Karim, Muhammad Hirzan Ifwad; Saari, Muhammad Arfa; Md Romzi, Muhammad Aiman Hakimi; Shaiful Azrizal, Muhammad Alif Haikal; Ahmad Jailani, Alif Ramdhan Naimullah (2025)
This study explores the role of Fiqh Muqaran (comparative Fiqh) in the formulation of modern fatwas and the reform of Islamic legal thought. It focuses on identifying the fundamental principles of comparative Fiqh and analysing its concept and historical development within Islamic scholarship. The research also examines the application of comparative Fiqh in addressing contemporary legal and social issues, particularly within pluralistic societies. Furthermore, it evaluates the strengths of this approach, such as its broad legal perspective and adaptability, as well as the challenges, including doctrinal differences and institutional constraints. The study also highlights how contemporary mujtahids and fatwa institutions approach inter-madhab differences in legal rulings to produce more comprehensive and context-sensitive decisions. This research aims to contribute meaningfully to the understanding of comparative Fiqh as a viable tool for contemporary Islamic legal reform.